Part I. Synthesis of chiral 3-substituted indanones via transition-metal-catalyzed reductive heck reaction. Part II. Tert-butyl peroxybenzoate promoted oxidative coupling between heteroarenes and alkanes - Lei, Kaining (Nanyang Technological University, 2018)
A new approach to chiral 3-substituted indanones via palladium-catalyzed reductive Heck reaction with excellent yields (>80%) and enantioselectivities (>90% ee) had been developed. Substrates with ortho-, para- substitution, or with electron-donating, electron-withdrawing groups on the phenyl ring could be tolerated. The ammonium salts, along with ethylene glycol could offer hydrogen-bonding, which help dissociate C-Br bond to promote a cationic pathway. A straightforward synthesis of chiral 3-substituted indanones via nickel-catalyzed reductive Heck reaction with good yields (>60%) and enantioselectivities (60%~80% ee) had been developed. A new strategy for building C-C bond between electron-deficient heteroarenes and cycloalkanes via oxidative coupling was developed. The reaction was promoted by TBPB and went through a radical pathway. No metal catalyst was needed. This method could build a wide range of alkyl heteroarenes which were useful in medicinal chemistry.